Somatosensory inputs by application of KinesioTaping: effects on spasticity, balance, and gait in chronic spinal cord injury - Tamburella, Federica; Scivoletto, Giorgio; Molinari, Marco (Frontiers in Human Neuroscience, 2014)
Introduction: Leg paralysis, spasticity, reduced inter limb coordination and impaired balance are considered the chief limitations to overground ambulation in subjects with incomplete spinal cord injury (SCI). In the last years KinesioTaping (KT) application has been proposed for enhancing sensory inputs, decreasing spasticity via proprioception feedback and relieving abnormal muscle tension. No studies addressed KT technique on SCI subjects: our goal was to analyze effects of ankle joint KT application on spasticity, balance and gait. Material and Methods: A randomized cross-over case control design was used to compare KT and conventional non-elastic silk tape (ST) application’s effects in 11 chronic SCI subjects, AIS level D, with soleus/gastrocnemius (S/G) muscles’ spasticity , balance and gait impairments. Treatment: 48 hours of either KT or ST treatment was followed after 1 week interval by a reverse protocol. Patient treated with KT were subjected to 48 hours of ST treatment and viceversa. Single Y-stripe of Cure©tape (KT) and ST were applied to S and G with 0% stretch. Before and after 48 hours of KT and ST application, clinical data of range of motion (ROM), spasticity, clonus, pain, balance and gait were collected. Stabilometric platform assessment of Centre of Pressure (COP) movements, bi-dimensional gait analysis and electromyograpich (EMG) activity of S, G, Tibialis Anterior and Extensor Hallicus Lungus muscles were also collected. Results: Only After KT treatment significant effects on spasticity, clonus and COP movements, kinematic gait parameters and EMG activities were recorded. Comparison between KT and ST improvements pointed out significant differences for ROM, spasticity, clonus, pain, COP parameters and most of all kinematic gait data. Discussion: KT short term application reduces spasticity and pain and improves balance and gait performances in chronic incomplete SCI subjects.